Dificultades emocionales y desarrollo lectoescritor en un niño con dislexia - Ayala Loja, Carolina Gardenia (Machala, Utmachala, 2023)
The present research work aims to establish how emotional difficulties affect the reading and writing development of a child with dyslexia in the seventh year of EGB of the school "Flavio Aguilar Hernández" in the city of Pasaje; for this purpose it has been necessary to elaborate specific objectives focused on the activities and strategies for the achievement of the general objective; In the same way, an analysis of the causes of the emotional difficulties that influence their reading and writing development, the evaluation of their reading and writing skills and emotional characteristics and the proposal of strategies for their intervention, improving their academic performance and overcoming their difficulties both in reading and writing and in the emotional field. This work is developed through a qualitative approach applying some research instruments for the collection of information, such as interviews with parents and teachers, the CAT-A test, the reading and writing test of Dr. Ricardo Olea, the same that are applied to the child; n important aspect of this research is that it is done around a child who has been diagnosed with Dyslexia. The scope of the research is descriptive and explanatory, which focuses on the analysis and understanding of the problem in order to explain the causes and effects of emotional difficulties in children, the subject of the research; thanks to this, different measurement instruments will be applied to measure and analyze the data, allowing a more accurate understanding of the problem under study. The results of the research allow understanding how emotional difficulties influence reading and writing development and how to intervene from the school and family environment, helping education professionals to address these problems and the parents of the children to better understand the need to strengthen the emotional environment of children at home.
El presente trabajo de investigación tiene como finalidad establecer de qué manera las dificultades emocionales afectan al desarrollo lecto escritor en un niño con dislexia del séptimo año de EGB de la escuela “Flavio Aguilar Hernández” de la ciudad de Pasaje ; para lo cual ha sido necesario elaborar objetivos específicos enfocados en las actividades y estrategias puntales para el alcance del objetivo general; de la misma manera realizar un análisis de las causales de las dificultades emocionales que influyen en su desarrollo lectoescritor, la evaluación de sus habilidades lectoescritoras y características emocionales y el planteamiento de estrategias para su intervención mejorando su rendimiento académico y superando sus dificultades tanto en la lecto escritura y el ámbito emocionales. Este trabajo se desarrolla a través de un enfoque de tipo cualitativo aplicando algunos instrumentos de investigación para la recolección de información, tales como, entrevistas dirigidas hacia los padres y docente, el test CAT-A, la prueba de lecto escritura del Dr. Ricardo Olea, las mismas que son aplicadas al niño; n aspecto importante de esta investigación es que se la realiza en torno a un niño que ha sido diagnosticado con Dislexia. El alcance en la investigación es el descriptivo explicativo el que se centra en el análisis y comprensión del problema y así poder explicar sus causas y efectos de las dificultades emocionales en el niño, sujeto de la investigación; gracias a esto se aplicaran diferentes instrumentos de medición que permitan medir y analizar los datos permitiendo una comprensión más precisa del problema de estudio. Los resultados que arroja la investigación permiten comprender como las dificultades emocionales influyen el desarrollo lecto escritor y como se puede intervenir desde el ámbito escolar y familiar, ayudando a los profesionales en educación abordar estas problemáticas y a los padres de los niños comprender de mejor manera la necesidad de fortalecer el ámbito emocional de los niños dentro del hogar.
Keywords: ÁMBITO EMOCIONAL; LECTOESCRITURA; DISLEXIA